Cooperative Learning for Distributed In-Network Traffic Classification - S.B. Joseph; H.R. Loo; I. Ismail; T. Andromeda; M.N. Marsono (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Inspired by the concept of autonomic distributed/decentralized network management schemes, we consider the issue of information exchange among distributed network nodes to network performance and promote scalability for in-network monitoring. In this paper, we propose a cooperative  learning  algorithm  for  propagation and  synchronization of network information among autonomic distributed network nodes for online traffic classification. The results show that network nodes with sharing capability perform better with a higher average accuracy of 89.21% (sharing data) and 88.37% (sharing clusters) compared to 88.06% for nodes without cooperative learning capability. The overall performance indicates that cooperative learning is promising for distributed in-network traffic classification.